2011
DOI: 10.1007/s00280-011-1581-4
|View full text |Cite
|
Sign up to set email alerts
|

Phase I trial of lestaurtinib for children with refractory neuroblastoma: a new approaches to neuroblastoma therapy consortium study

Abstract: Purpose TrkB acts as an oncogenic kinase in a subset of human neuroblastomas. Lestaurtinib, a multi-kinase inhibitor with potent activity against Trk kinases, has demonstrated activity in preclinical models of neuroblastoma. Methods Patients with refractory high-risk neuroblastoma received lestaurtinib twice daily for 5 days out of seven in 28-day cycles, starting at 70% of the adult recommended Phase 2 dose. Lestaurtinib dose was escalated using a 3 + 3 design. Pharmacokinetics and plasma phospho-TrkB inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 24 publications
0
62
0
Order By: Relevance
“…No TRKA inhibitors were explored in clinical trials with the possible exception of lestaurtinib (CEP-701), a staurosporine-derivative multikinase inhibitor that was investigated in clinical settings with reported TRKA overexpression, without evidence of efficacy (7,38). However, recent studies that have identified recurring oncogenic NTRK1 rearrangements in subsets of NSCLC and colorectal carcinoma patients (11,12), as well as other studies suggesting a potential role of activated TRKA in other tumor types, including glioblastoma and Spitz melanoma (14)(15)(16)39), have created much renewed interest in the identification and clinical investigation of effective TRKA inhibitors (13).…”
Section: Discussionmentioning
confidence: 99%
“…No TRKA inhibitors were explored in clinical trials with the possible exception of lestaurtinib (CEP-701), a staurosporine-derivative multikinase inhibitor that was investigated in clinical settings with reported TRKA overexpression, without evidence of efficacy (7,38). However, recent studies that have identified recurring oncogenic NTRK1 rearrangements in subsets of NSCLC and colorectal carcinoma patients (11,12), as well as other studies suggesting a potential role of activated TRKA in other tumor types, including glioblastoma and Spitz melanoma (14)(15)(16)39), have created much renewed interest in the identification and clinical investigation of effective TRKA inhibitors (13).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of TrkB in pediatric NB is associated with an unfavorable prognosis and resistance to chemotherapy. In a phase I clinical trial, the TRK inhibitor lestaurtinib has been shown to induce stabilization of disease in recurrent/refractory NB [34]. Combining conventional chemotherapy with more specific Trk inhibitors (e.g.…”
Section: Molecular Pathogenesismentioning
confidence: 99%
“…Of important consideration to our studies, CEP‐701 also increases CD30L, which could support the survival of NPM‐ALK + T‐cell lymphoma (Atsaves et al ., 2014). Although the CEP‐751‐related compounds have been utilized in clinical trials of patients with cancer (Chan et al ., 2008; Hexner et al ., 2014; Knapper et al ., 2006; Minturn et al ., 2011; Santos et al ., 2010), we decided not to use these compounds in our study because of the concerning issues listed above. Instead, we used the TrkAi, which has been recently shown to induce significant inhibitory effects on TrkA without known effects on other targets (Kokona et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%